Etude bioécologique de l’entomofaune de deux espèces d’agrumes (oranger et citronnier) dans la région de Mostaganem - KRACHE, Feriel; BENDENIA, Soraya (My University, 2018)
The ecological and biological interest of the study of the dynamics and the inventory of the entomological fauna was highlighted by this modest work highlighting the great biodiversity reported in the three orchards of citrus studied, in the experimental farm of the University of Mostaganem. This site is located in the municipality of Mazagran. To realize the population dynamics and the inventory of the citrus entomofauna, we took samples from the leaves, with a determination of the species at the laboratory levels. These methods allowed us to identify a significant number of species, which were 66 species, which corresponds to eight taxonomic orders including Diptera, Coleoptera, Hemiptera, Hymenoptera, Neuroptera, Lepidoptera, Psocoda and Thysanoptera. We discerned eight diets (predators, parasitoids, defoliators, mycetophagous, omnivorous, saprophagous, xylophagous and scavenger). In addition, the population dynamics revealed a significant infestation of Parlatoria ziziphi on orange and lemon trees with values of 100% from the first day of sampling.
Keywords: Mostaganem; Agrumes; Entomofauna; Population Dynamics; Inventory.; Agrumes; Entomofaune; Dynamique de populations; Inventaire